Tractatus Hoffmeyerensis: Biosemiotics as expressed in 22 basic hypotheses - Stjernfelt, Frederik (Sign Systems Studies, 2002)
This paper briefly outlines the main ideas of biosemiotics in 22 hypotheses, with special regards to the version of it claimed by Jesper Hoffmeyer.